Spirooxazine Photoisomerization and Relaxation in Polymer Matrices - Maria Larkowska; Michael Wuebbenhorst; Stanislaw Kucharski (International Journal of Polymer Science)
9′-Hydroxy-1,3,3-trimethylspiro[indoline-2,3′[3H]naphtha[2,1-b]-1,4oxazine] (SPO-7OH) was used in studies of photochromic transformations in polymer matrices. Illumination with UV lamp caused opening the spirostructure of the oxazine with formation of open merocyanine species absorbing at ca. 610 nm. The kinetic studies of thermal relaxation of the open form showed that this process can be described with a biexponential function including both photochemical reaction and rheological behaviour of the polymeric environment. Basing on Arrhenius plot of the rate constant ascribed to the photochemical reaction, the activation energy was determined, which was 66.1 and 84.7 kJ/mole for poly(methyl methacrylate-co-butyl methacrylate) and poly(vinylpyrrolidone) matrix, respectively.